2010
DOI: 10.1186/1746-1340-18-26
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 2-regulated in vitro antibody production following a single spinal manipulative treatment in normal subjects

Abstract: BackgroundOur recent investigations have demonstrated that cell cultures from subjects, who received a single spinal manipulative treatment in the upper thoracic spine, show increased capacity for the production of the key immunoregulatory cytokine, interleukin-2. However, it has not been determined if such changes influence the response of the immune effector cells. Thus, the purpose of the present study was to determine whether, in the same subjects, spinal manipulation-related augmentation of the in vitro i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 20 publications
0
33
1
Order By: Relevance
“…In addition, cortisol is a potent anti-inflammatory and helps one cope with stress [47]. Cervical SM can influence inflammatory and immune biomarkers including cortisol [9,48,49]. Our findings differed from the findings of Plaza-Manzano et al [19] who reported a significant change in cortisol following a SM study on asymptomatic individuals but not in the control group.…”
Section: Cortisolcontrasting
confidence: 88%
“…In addition, cortisol is a potent anti-inflammatory and helps one cope with stress [47]. Cervical SM can influence inflammatory and immune biomarkers including cortisol [9,48,49]. Our findings differed from the findings of Plaza-Manzano et al [19] who reported a significant change in cortisol following a SM study on asymptomatic individuals but not in the control group.…”
Section: Cortisolcontrasting
confidence: 88%
“…The latter authors suggested that such down regulation of inflammatory cytokines as they observed was likely not mediated by substance P, but might have been the result of activation of the parasympathetic nervous system. Using a comparable design, they also demonstrated increased synthesis of immunoglobulin G and immunoglobulin M at 20 min and 2 h, respectively, following thoracic manipulation (Teodorczyk-Injeyan et al, 2010). Collectively, these results do not paint a cohesive picture of the effects of spinal manipulation on the complex interactions within the immune system.…”
Section: Somato-humoural Studiesmentioning
confidence: 57%
“…The literature search on MEDLINE, Google Scholar, and ProQuest retrieved 1707 records and nine articles were included as they met the inclusion criteria [23,24,25,26,27,28,29,30,31]. The manual search yielded four additional manuscripts totaling 13 relevant articles.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies examined cortisol levels through saliva samples [30,31,32,34,35], whereas four used the venepuncture technique [24,25,26,33]. Four studies examined the effects of SMT on the immune system and all of them were conducted on healthy individuals [23,27,28,29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation